ANALISIS SEMANGAT KERJA APARATUR DESA PADA DESA RAMBAH TENGAH UTARA KABUPATEN ROKAN HULU - ARLENI, IRMA (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
Irma Arleni. 1125030. 2015. Morale Apparatus Village On Desa RambahTengah Utara Kabupaten Rokan Hulu. Coach 1 Asrori, S.Pd., MM. Coach 2Welven Aida, S.Pd., M.Pd.This study aims to identify and analyze morale in the village Apparatus on DesaRambah Tengah Utara Kabupaten Rokan Hulu. Population and samples takenwere 31 people of the total number of village officials Rambah Tengah UtaraKabupaten Rokan Hulu. This study population using census method that is theamount of the overall population used as a sample. From the research that moraleat the village officials Desa Rambah Tengah Utara Kabupaten Rokan Hulu seen ofcooperation are in the category quite well with the percentage of 73%, andDiscipline are in the unfavorable category with a percentage of 53%, whileattendance in the unfavorable category with a percentage of 53% andresponsibilities are in the category quite well with the percentage of 73%. Fromthe conclusions that have been raised, it can search its results mean that morale inthe village of Desa Rambah Tengah Utara Kabupaten Rokan Hulu are in theunfavorable category with a percentage of 63%.Keywords: Morale